Antibiotic Sensitivity Pattern of Helicobacter pylori in Dyspeptic Patients in Kano, Nigeria - Bello, Ahmad K.; Borodo , Mohammad M.; Yakasai , Ahmad M.; Tukur , Abubakar D. (Current Overview on Disease and Health Research Vol. 2, 2022)
Helicobacter pylori (H. pylori) are common and believed to infect half of the world’s population. H. pylori eradication dramatically affects the natural history of peptic ulcer and gastric lymphoma; however, antibiotic resistance is recognised increasingly as a contributing factor in a number of patients who fail H. pylori eradication therapy. Numerous diseases associated with H. pylori have been well established; therefore it is important that the antibiotic sensitivity pattern of H. pylori be evaluated to allow for effective eradication of the organism in appropriate patient population. Questionnaires were administered to obtain relevant biodata. During endoscopy gastric biopsy specimens were obtained and cultured using Columbia blood agar media (Oxoid Ltd, England) incubated at 37°C for H. pylori identification. The sensitivity pattern of isolates was assessed using the disc diffusion method. Each patient's pre- and post-treatment stool samples were taken for the H. pylori faecal antigen test to determine the eradication rate. H. pylori was 100% sensitive to levofloxacin and clarithromycin, but only 9.2% sensitive to amoxicillin. Other tested antibiotics were found to be 100% resistant. The prevalence of H. pylori was 81.7% using histology. This study revealed a significant amoxicillin resistance rate; however, clarithromycin and levofloxacin exhibited high sensitivity (100 %). We suggested that levofloxacin be adopted in preference to amoxicillin as part of triple therapy for H. pylori eradiation in Nigeria.